Предмет:
МатематикаАвтор:
jada1
S=(a+b)/2 * h
2S/h = a+b
a= 2S/h - b
b=2S/h - a
2
h = vt + gt^2/2
vt = h - gt^2/2
v = (h - qt^2/2)/t
gt^2/2 = h - vt
g = 2(h - vt)/t^2
3
1/R = 1/R1 + 1/R2
1/R1 = (1/R - 1/R2)
R1=1/(1/R - 1/R2) = R*R2/(R2-R)
1/R2 = (1/R - 1/R1)
R2=1/(1/R - 1/R1) = R*R1/(R1-R)
Автор:
victoria31Добавить свой ответ
Предмет:
ЛитератураАвтор:
larissaytryОтветов:
Смотреть
Предмет:
МатематикаАвтор:
bootie9fqfОтветов:
Смотреть
Предмет:
МатематикаАвтор:
dud0lgbОтветов:
Смотреть
Предмет:
Английский языкАвтор:
benny50Ответов:
Смотреть